Nafkah Isteri Bekerja: Satu Tinjauan Di Daerah Pasir Mas Kelantan - Wan Hasssan, Wan Zulkifli; Abdullah, Nabilah (Jurnal Fiqh, 2010)
In Muslim marriage system, it is a duty of a husband to give maintenance to his family, and a wife is responsible to household matters. But in modern society, some wives are also going out to work and to help in financial support to the family. This study discusses the concept of working wives in Islamic perspective by analyzing Muslim jurist?s views on maintenance and the ethics of the working wives. To get a real picture on this, a field study employing questionnaire methods have been done, where 150 working wives in the District of Pasir Mas, Kelantan have been selected randomly as the samples. The data collected are analyzed and presented in table. The study finds that the majority husbands of the working wives are still carrying out their duty of providing subsistence to their wives and the majority of the working wives have generously support their husbands in their family financial aspects.